Genetic algorithms in engineering systems - Zalzala, A. M. S. (Ali M. S.).; Fleming, P. J. (Peter J.). (London, United Kingdom Institution of Electrical Engineers, 1997)
The book reviews developments in the following fields: multiobjective genetic algorithms; scaleable neural architecture evolution; chaotic systems identification; job shop scheduling; evolutionary algorithms; aerodynamic inverse optimisation problems; and VLSI layout genetic design.
Electronic reproduction.
Keywords: Systems engineering -- Mathematics -- Congresses; Genetic algorithms -- Congresses; Computer-aided engineering -- Congresses; Electronic books